Upgrade of Thomson Scattering Diagnostic on HL-2A - Wenping Guo; Yuan Huang; Chunhua Liu; Zhen Feng; Zhipei Hou; Wenyan Zhai; Hisamichi Funaba; Ichihiro Yamada; Yonggao Li; Zhongbin Shi (Instruments, 2023)
The Thomson scattering diagnostic of the HL-2A tokamak device was upgraded to improve its multi-point diagnostic capability, including new collection optics, fibers bundles, and data analysis code. The small old collection lens was replaced by a six-piece lens with a Cooke optical design. The aperture of its first standard sphere face is 310.125 mm, which successfully increases the amount of collected scattering light by about three times. The new collection optic module allows for up to twenty-six spatial points. A kind of Y-type fiber bundle has also been used to ensure that the fiber end-face matches the image of the laser beam exactly. Additionally, the new data analysis code can provide preview results in seconds. Finally, the multi-point <semantics>Te</semantics> diagnostic ability has been significantly improved.